Fundamental principles of occupational health and safety - Alli, Benjamin O. (Geneva, 2001)
"This practical guide to developing effective occupational health and safety policies and programmes focuses on the key topics essential to promoting health and safety in the workplace. It presents a concise overview of the issues involved, together with specific guidelines for policy design and implementation at both national and enterprise levels. The operational aspects of meeting health and safety requirements are also covered, with detailed sections on legislation and enforcement, occupational health surveillance, and preventive and protective measures, as well as health education and training. At a time of increased awareness of the need to combat occupational accidents and diseases, this topical book provides vital information on national laws, labour codes and regulations governing workers' health and safety. It also explains the main concepts in occupational health and demonstrates how relevant ILO Conventions and Recommendations define workers' rights and allocate duties and responsibilities to competent authorities, employers and workers. It considers the respective roles of employers and workers in the management of occupational health and safety, and gives examples of good practice on such pivotal issues as surveillance of workers' health and of the working environment, the functions of occupational health services, and ways of reducing the incidence of work-related injuries and diseases. The volume provides a wealth of practical advice for authorities, employers and workers alike, along with a glossary, a list of related publications and an example of a health and safety policy."